Hybrid Community Empowerment for Indonesian Migrant Workers: Strengthening Financial and Entrepreneurial Capacity in Malaysia and Thailand - Fatwa Zuhaena; Heru Cahyo; Abdul Gader Salem Balafif; Agista Suti Rahmawati; Ardiyanti Suryaning Tiyas (CITAKARYA, 2025)
Indonesian migrant workers frequently encounter challenges related to financial preparedness, economic sustainability, and long-term post-employment planning while working abroad. These conditions highlight the importance of sustainable empowerment initiatives capable of strengthening adaptive economic resilience among migrant communities. This community service program aimed to develop a hybrid community empowerment model for Indonesian migrant workers in Malaysia and Thailand through integrated online and onsite mentoring activities. The program involved 42 participants and was implemented through several stages, including preliminary online counseling, onsite mentoring and empowerment sessions, and post-program virtual evaluation. The first implementation was conducted during September–October 2025, while the second program was carried out in March–May 2026. A participatory community assistance approach was applied using reflective discussion, collaborative mentoring, and sustainable monitoring mechanisms. The findings demonstrated increased participant awareness regarding financial literacy, entrepreneurial preparation, and adaptive economic management. The hybrid empowerment model also facilitated continuous interaction and participatory engagement despite geographical limitations. Furthermore, collaborative involvement between lecturers and students strengthened intercultural learning and community participation throughout the empowerment process. This program contributes to the development of sustainable transnational community empowerment practices by proposing an adaptive hybrid mentoring framework integrating digital communication and direct social engagement.